Facial attractiveness of Class II patients treated with functional appliances: a systematic review and comparative assessment - Freitas, Jessica Quereza de (2025)
Introduction: Facial esthetics plays a decisive role in treatment acceptance and patient satisfaction. Class II malocclusion, frequently associated with mandibular retrusion, is commonly treated with functional appliances, which may influence profile attractiveness. Objective: Two complementary investigations: (1) a systematic review synthesizing available evidence on the esthetic perception of facial profiles in Class II patients treated with functional appliances; and (2) a retrospective comparative study evaluating changes in profile attractiveness in patients treated with Twin Block and Jasper Jumper appliances, as perceived by orthodontists and laypeople. Methods: The systematic review followed PRISMA guidelines, included 21 retrospective studies, and assessed risk of bias with ROBINS-I V2. The comparative study analyzed 24 patients (12 Twin Block; 12 Jasper Jumper), with silhouettes evaluated by 35 orthodontists and 35 laypeople using a 10-point scale. Statistical analyses included Wilcoxon, MannWhitney, Chi-square, and Fishers exact tests (p < 0.05). Results: From 330 records, 21 retrospective studies involving 776 patients were included. Most studies reported improvements in facial profile attractiveness after functional appliance therapy, regardless of appliance type. The systematic review confirmed that functional appliances generally improve profile attractiveness, although the magnitude of improvement varies according to appliance type, patient characteristics, and evaluator background. No appliance demonstrated clear superiority. The comparative study showed significant esthetic improvements for both appliances. Although the Jasper Jumper group consistently received higher absolute scores, the changes from pretreatment to posttreatment (T2T1) did not differ significantly between the appliances. Orthodontists tended to assign higher scores than laypeople, particularly for Jasper Jumper profiles. Conclusions: Functional appliances generally enhance facial profile attractiveness in Class II patients. Improvements are not uniform across appliances or evaluators, and the strength of evidence is limited by retrospective designs, methodological heterogeneity, and uncontrolled confounders. Twin Block and Jasper Jumper appliances significantly enhanced the esthetic perception of Class II patients with mandibular retrusion. Although Jasper Jumper obtained higher absolute ratings, both appliances produced comparable improvements in facial esthetics. Registration: This SR was registered in PROSPERO CRD42020207265. Funding: Coordination for the Improvement of Higher Education Personnel - Brazil (CAPES), Finance Code 001.